Regulação de tecnologias e arquitetura de sistemas : um estudo sobre o privacy by design e a transparência aplicada a algoritmos computacionais - Morassutti, Bruno Schimitt (2019)
The remarkable development and propagation of information technology has resulted in profound outcomes in our society, affecting fundamental rights of groups and individuals. This scenario of incremental and disruptive shifts stimulates the need to study the stresses between Law, Science, Technology and Innovation. In light of this situation, the regulation of electronic systems and computer algorithms has received considerable attention from scholars and regulatory agents who started to propose new methodologies for the protection of fundamental rights. Among these new methodologies is the privacy by design, which proposes the adoption of transparency as one of its foundational principles. Because of the novelty of the subject in Brazil, this research seeks to study the relationship between the transparency principle and privacy protection in the context of technology regulation. For that matter, the contributions of US the law doctrine about technology regulation are studied, in order to identify the reflections brought by different doctrinal phases. Likewise, the normative development of privacy by design was studied as well as its operationalization according to recent legislation. Finally, the enforcement of privacy by design with regard to computer algorithm transparency was studied in order to identify its reach and boundaries. It was concluded that under a technological point of view, algorithmic transparency faces limitations encountered by Computer Science itself. Because of that, a further increase in organizational transparency is needed in order to promote the responsible development of new technologies and to protect constitutionally assured fundamental rights.